Analisis Faktor–faktor yang mempengaruhi minat mahasiswa berinvestasi di aplikasi bibit - Mayang Azzahra Dika Ramadhani; Dewi Kusumowati; Wahyu Setiyorini (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
Based on observations of students who have invested, many of them use the Bibit App. Apart from the low initial investment cost, they also trust the Bibit App because it is registered with the Financial Services Authority (OJK). The Bibit App was created with the aim that people can immediately start investing easily and get risks that match their financial goals. This study was conducted to examine whether perceived benefits, perceived convenience, investment risk and investment knowledge have an influence on student interest in investing in the Bibit Application. This study uses a sample of undergraduate students at Merdeka University of Malang who have and have used the Bibit Application as a means of investment with a total of 64 respondents. This research method is quantitative research, the data obtained through google form is a type of primary data. The data in this study were processed using the SPSS (Statistical Package for Social Sciens) version 23 application. This study shows the results that perceived benefits and investment risk have an influence on student interest in investing in the Bibit Application. Meanwhile, perceived convenience and investment knowledge have no influence on student interest in investing in the Bibit Application.